Euro Area Policies : Staff Report for the 2015 Article IV Consultations with Member Countries. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
Context. The recovery is strengthening, underpinned by lower oil prices and the ECB's expanded asset purchase program. But the medium-term outlook remains weak, weighed down by the legacies of insufficient demand, lagging productivity, and weak bank and corporate balance sheets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet